Transcriptional modulation of squalene synthase genes in barley treated with PGPR - Yousaf, Anam; Qadir, Abdul; Anjum, Tehmina; Ahmad, Aqeel (Frontiers in Plant Science, 2015)
Phytosterol contents and food quality of plant produce is directly associated with transcription of gene Squalene Synthase (SS). In current study, barley plants were treated with different rhizobacterial strains under semi controlled (27±3°C) greenhouse conditions in order to modulate expression of SS gene. Plant samples were analysed through semi-quantitative PCR to evaluate effect of rhizobacterial application on transcriptional status of squalene synthase. Results revealed that among four SS genes (i.e. SSA, SS1, SS2 and SS3), the most expressive gene was SSA; while, SS2 was screened out as the second best induced gene due to Acetobacter aceti. The most efficient bacterial strain which recorded maximum gene expression was A. aceti AC8. Moreover, AC7 was reported as the least efficient bacterial species for inducing SS gene expression. AC8 enhanced the share of SSA and SS2 up to 43% and 31%, respectively. The study also described ribosomal sequence of the most efficient bacterial strain AC8, which was used to determine its phylogenetic relationships with other microbial strains. The study would be helpful to improve quality of plant produce by modulating transcription of SS genes.